MARINE ACOUSTIC SIMULATION MODEL AND ITS APPLICATION TO UNDERWATER ACTIVITIES IN THE VIETNAM’S SEA - Thao, Nguyen Van; Toan, Du Van (Vietnam Journal of Marine Science and Technology, 2015)
The basic researches on hydroacoustics in Vietnam are very limited, especially in the field of sound propagation simulation, while the world has many researches and positive application in underwater activities and marine fishery. Consequently, there is now a shortage of information to visualize the importance of sound propagation in the sea. In Vietnam, these is a growing need to secure the safety of the equipment, submarine, fishery and systematically arrange the hydroacoustic means in orher to provide and obtain the best hydroacoustic information, as well as to avoid detection of the enemy. The underwater acoustic channel has been indentified off Central Vietnam at 1260 m depth and acoustic speed is 1490 cm/s. This report presents research methods and acoustic simulation models, together with the simulation results that ensure the reliability sound through the underwater acoustic channel.